ANALISIS VARIABEL ANTESEDEN PERILAKU AUDITOR INTERNAL DAN KONSEKUENSINYA TERHADAP KINERJA (Studi pada di BUMN Kota Semarang) - Hanny Larasati; Herry Laksito (Diponegoro Journal of Accounting, 2013)
This study aims to analyze and provide empirical evidence of influence culture organizational, leadership style, and monetary incentive as antecedent of organizational commitments, while time budget pressure, task complexity, and discussion of audit review as antecedent of motivation. This study is also examine the consequence of commitment organizational and motivation on the performance of internal auditor. The sample of this research is the auditor employed in state-owned business entities. this research was conducted with methods of survey of auditors who are in state-owned enterprises Semarang.Samples taken with uses the technique purposive judgment of sampling. The criteria is an auditor who work on the state in the city of semarang, registered in the Compartments IAI Directory Public Accountant in 2012, and having experience working at least one year. The data conducted using a questionnaire propagated as much as 90 and only 58 a questionnaire that can be processed. Analysis of data analysis using methods path.This research using program SPSS version 16.0 stating that organizational culture, leadership style, monetary incentive have positive effect on organizational commitment . Time budget pressure and discussion of audit review impact on motivation while task complexity have negative effect on motivation. Organizational commitment and motivation have positive effect on performance, while organizational culture, monetaryincentive, and time budget pressure have no effect on the performance of auditors.